2008
DOI: 10.1002/ange.200804888
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Cross‐Couplings of Racemic α‐Bromoketones with Arylzinc Reagents

Abstract: Ohne Aktivatoren: Eine katalytische asymmetrische Kreuzkupplung von Arylzinkreagentien mit α‐Bromketonen wurde entwickelt (siehe Schema). Die stereokonvergente Kohlenstoff‐Kohlenstoff‐Verknüpfung verläuft unter ungewöhnlich milden Bedingungen und eignet sich so zum Aufbau potenziell labiler tertiärer Stereozentren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 27 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Following the initial disclosures the authors have demonstrated the exceptionally wide scope of the transformation, with efficient couplings of primary and secondary alkyl chlorides, bromides, iodides, carbonates, and sulfonates with alkyl-, vinyl-, and arylzinc nucleophiles (Figure 4). 45,46,47,48,49,50,51,52,53,54 Furthermore, the authors have also developed conditions for enantioselective Suzuki, 55,56,57,58,59,60 Hiyama, 61 Kumada, 62 and zirconium-Negishi 53,63 couplings with a variety of alkyl electrophiles.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…Following the initial disclosures the authors have demonstrated the exceptionally wide scope of the transformation, with efficient couplings of primary and secondary alkyl chlorides, bromides, iodides, carbonates, and sulfonates with alkyl-, vinyl-, and arylzinc nucleophiles (Figure 4). 45,46,47,48,49,50,51,52,53,54 Furthermore, the authors have also developed conditions for enantioselective Suzuki, 55,56,57,58,59,60 Hiyama, 61 Kumada, 62 and zirconium-Negishi 53,63 couplings with a variety of alkyl electrophiles.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…The difficult issue of cross-coupling with secondary halides [125] having β-hydrogens has been addressed with nickel catalysts. In the presence of NiCl 2 ·glyme and the appropriate enantiopure Pybox ligand (269 or 273), arylzincs can react with racemic propargyl halides [205] or racemic α-bromo-ketones [206] to provide the corresponding coupling products in excellent yields and with good enantioselectivities as shown for 268 and 272 (Scheme 4.60). Note, however, that the electrophiles are somewhat activated.…”
Section: Cross-coupling With C(sp 3 )-Electrophilesmentioning
confidence: 99%
“…Styrenylzinc reagents are also valuable nucleophiles in this crosscoupling reactions, but their stereoselectivity is low. Scheme 4.60 Ni-catalyzed cross-coupling of arylzincs with secondary halides [205,206].…”
Section: Cross-coupling With C(sp 3 )-Electrophilesmentioning
confidence: 99%
“…[8] In an umpolung approach, Fu et al reported asymmetric coupling between a-haloketone electrophiles and arylmetal reagents. [9] Herein, we report the first palladiumcatalyzed coupling of ketones to produce tertiary centers with excellent ee values [Eq. (5)].…”
mentioning
confidence: 99%